2009
DOI: 10.1089/ten.tea.2008.0203
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Polymer/Bioactive Glass-Composite Microporous Spheres for Tissue Regeneration Applications

Abstract: Conformable scaffold materials capable of rapid vascularization and tissue infiltration would be of value in the therapy of inaccessible wounds. Microporous spheres of poly(D,L-lactide-co-glycolide) (PLGA) containing bioactive glass (BG) were prepared using a thermally induced phase separation (TIPS) technique, and the bioactivity, in vitro degradation, and tissue integration of the microporous spheres were assessed. Microporous spheres containing 10% (w/w) BG stimulated a significant increase in vascular endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 26 publications
1
58
1
Order By: Relevance
“…29 We have also shown that TIPS microspheres retain an open scaffold structure when implanted in vivo, which facilitates rapid tissue infiltration and integration at the site of implantation, thus reducing the possibility of migration from the target site. 40 Results from the current study indicate that it is possible to achieve smooth muscle-like cells from AdMSCs when incubated on TIPS microcarriers. Further studies will be necessary to prove that the differentiated cells are capable of providing phasic and tonic contractile properties similar to native smooth muscle and that they can restore damaged or lost smooth muscle function.…”
Section: Figmentioning
confidence: 62%
See 1 more Smart Citation
“…29 We have also shown that TIPS microspheres retain an open scaffold structure when implanted in vivo, which facilitates rapid tissue infiltration and integration at the site of implantation, thus reducing the possibility of migration from the target site. 40 Results from the current study indicate that it is possible to achieve smooth muscle-like cells from AdMSCs when incubated on TIPS microcarriers. Further studies will be necessary to prove that the differentiated cells are capable of providing phasic and tonic contractile properties similar to native smooth muscle and that they can restore damaged or lost smooth muscle function.…”
Section: Figmentioning
confidence: 62%
“…29,31,40 Relative to solid microcarriers, TIPS microcarriers of an equal size contain approximately 80-90% less polymer material. 40 This is advantageous as less degradation products are produced as the microcarriers degrade to be replaced by host tissue. The open porous structure also allows surface erosion to occur rather than an autocatalytic process that is associated with solid PLGA microspheres due to entrapment and accumulation of acidic degradation products.…”
Section: Figmentioning
confidence: 99%
“…In vivo results have confirmed that BG is able to stimulate and promote neo-vascularization [52,55,[120][121][122]164,203,206,[208][209][210][211]. For example, Leu et al [211] filled calvarial defects in SpragueDawley rats with 45S5 Bioglass ® impregnated (1.2 mg) collagen sponges (volume = 0.05 cm 3 ) and unloaded, empty sponge as a control.…”
Section: Effect Of Bioactive Glass On Angiogenesismentioning
confidence: 92%
“…In 2003, Boccaccini and Maquet [42] reported for the first time on the successful fabrication of porous foam-like bioactive glass containing poly(lactide-co-glycolide) (PLGA) composites, which exhibited well-defined, oriented and interconnected porosity. Since then, many studies have been carried out to optimize and investigate bone TE composite scaffolds concerning material combinations, bioactive properties, degradation characteristics [161,164,165,168], in vitro [47,[161][162][163]169] and in vivo behavior [47,164], as well as mechanical properties [50,81,160].…”
Section: Bioactive Glass Containing Composite Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation